Application In Locker Security System With Double Bluetooth Media Using Microcontroller And Basic Programming Language(Aplikasi Sistem Double Security Pada Locker Dengan Media Bluetooth Menggunakan Mikrokontroler Dan Bahasa Pemrograman Basic) - Risa Nadia Ernes (Jurnal KomtekInfo, 2020)
This study was conducted to design a security system on a locker by implementing multiple security using bluetooth media on the mobile phone and the keypad so that it can improve the security of a good value. The system is built to design, create and implement the components of a system that includes a microcontroller as process controllers, mobile phones (Bluetooth) based on android and bluetooth module HC-05 as the sender and recipient of the data series that serve as the first security in the form of a data connection and keypad as the security of both the locker system. Both security serves as input into a double security system. This system has outputs that can display information, the activation open the door and close the door and buzzer as a marker that the password is incorrect.The results showed a tool created to function properly and can be expanded to a larger scale.